Growth of nanostructured zinc oxide on flexible conductive substrate: a review - Ainuddin, Ainun Rahmahwati; Mohd Ismail, Siti Sarah; Kamdi, Zakiah; Hussin, Rosniza; Ibrahim, Siti Aida (Trans Tech Publications Ltd, Switzerland, 2022)
In this paper, a review on the structural and morphological of nanostructured zinc oxide (ZnO) fabricated on flexible conductive substrate, mainly indium tin oxide coated on polyethylene terephthalate (ITO/PET) via various fabrication method is reported. Besides fabrication method, the effect of fabrication condition such as immersion time of ZnO-ITO/PET via hydrothermal method, concentration of modification material of precursor solution via sol-gel method, value of applied cathodic voltage and value of current densities via electrochemical deposition are also discussed. XRD analysis showed that the growth of ZnO-ITO/PET are preferred on (002) or (101) planes. SEM analysis revealed various type of nanostructured ZnO when prepared by sol-gel, spin coating, HWT and hydrothermal method, highlighting ZnO nanorods as the main morphology of ZnOITO/PET. The diameter of ZnO nanorods ranges from 10 nm to 830 nm.